2006
DOI: 10.1088/0953-8984/19/1/016007
|View full text |Cite
|
Sign up to set email alerts
|

Noble gas films on a decagonal AlNiCo quasicrystal

Abstract: Abstract. Thermodynamic properties of Ne, Ar, Kr, and Xe adsorbed on an Al-NiCo quasicrystalline surface (QC) are studied with Grand Canonical Monte Carlo by employing Lennard-Jones interactions with parameter values derived from experiments and traditional combining rules. In all the gas/QC systems, a layer-by-layer film growth is observed at low temperature. The monolayers have regular epitaxial fivefold arrangements which evolve toward sixfold close-packed structures as the pressure is increased. The final … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 38 publications
1
34
1
Order By: Relevance
“…Therefore in one case, the interaction of Pb atoms adsorbed with the quasiperiodic Al-rich plane is highly corrugated, a factor that promotes the 2D pseudomorphic growth. 15,20 On the other side, the interaction between the Pb adsorbate and the fcc Al͑111͒ plane must be flatter in order to promote the formation of the observed moiré structure. Previous studies of Pb on Cu͑111͒ reported 3D island growth upon deposition at room temperature.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore in one case, the interaction of Pb atoms adsorbed with the quasiperiodic Al-rich plane is highly corrugated, a factor that promotes the 2D pseudomorphic growth. 15,20 On the other side, the interaction between the Pb adsorbate and the fcc Al͑111͒ plane must be flatter in order to promote the formation of the observed moiré structure. Previous studies of Pb on Cu͑111͒ reported 3D island growth upon deposition at room temperature.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Once it has been completed, a structural transition toward a crystalline structure usually occurs. This transition has been investigated, for example, for the case of Xe layers physisorbed on the tenfold surface of d-Al-Ni-Co. 15,20 Both LEED experiments and grand canonical Monte Carlo simulations demonstrated that the film is epitaxial in the first layer but evolves into a bulklike sixfold structure in the second layer. A molecular-dynamics study of the structure of adlayers on a quasicrystalline substrate pointed out the importance of the adatom-adatom interactions with respect to the adatom-substrate interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Since they show exceptional material properties [3], there is much interest in understanding and controlling the growth of quasicrystals. Therefore, a lot of research has been devoted to study the ordering of atoms on quasicrystalline surfaces [4][5][6][7][8][9][10][11][12][13][14][15]. However, in these experiments it is very difficult to determine the exact positions of the atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulations reported in Refs. [11,12] the external field was created by the surface of a QC. The question then arises: Can 2D QCs also be formed in monolayers on crystal surfaces of simple square symmetry?…”
mentioning
confidence: 99%
“…Computer simulations of adsorption of noble gases on QC surfaces [11,12] showed that monolayer films may exhibit a regular epitaxial fivefold arrangement of atoms, which evolves toward a sixfold, close-packed structure as the pressure increases. The structures and phase transitions observed were due to the specific symmetry of the field over the QC surface and correlated with the mismatch between the adsorbate and the substrate characteristic lengths.…”
mentioning
confidence: 99%